TEHNIK MARKETING PRODUK PADA YAYASAN PONDOK PESANTREN - Arofah, Triani; Maghfiroh, Siti; Sunarmo, Agus; Purwati, Atiek Sri; Widianingsih, Rini (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
The aim of this community service activity is to transfer information and knowledge to Islamic boarding school managers so that they have marketing technical skills in marketing products. The activity participants consisted of teachers and managers of the Bahrul Uulum Purbalingga Islamic Boarding School Foundation, Central Java. The training method is implemented by providing training, mentoring on marketing techniques and question and answer discussions. It is hoped that the results of the activity will be able to contribute to the Bahrul Uulum Islamic Boarding School in terms of improving skills and usefulness as an alternative source of additional income. Recommendations for further activities include training related to managing cost calculations in making bouquets and other marketing costs.